De identificatie van een zilveren microscoopje van Antoni van Leeuwenhoek (1632-1723) - Cocquyt, Tiemen (Studium, 2016)
A hitherto unknown silver microscope of the famous Delft microscopist Antoni van Leeuwenhoek has been identified as genuine, thanks to an intensive investigation using various modern forensic techniques. In this research the preserved Leeuwenhoek microscopes with known provenance were used as a benchmark. It is argued that for a reliable judgement about the authenticity of an object a holistic approach is required: a forensic investigation needs to assess its origin, style characteristics, material properties and production techniques, as well as ’connoisseurship’ and the object’s publication history. In this paper all these aspects and their pitfall are discussed. The optical research has shown that the newly discovered instrument has a blown lens (similar to the Utrecht Leeuwenhoek microscope), with a magnification of 248 times, which makes it one of the strongest magnifying Leeuwenhoek microscopes preserved.